Regulation of eotaxin‐3/CC chemokine ligand 26 expression by T helper type 2 cytokines in human colonic myofibroblasts. (4th July 2013) - Takahashi, K.; Imaeda, H.; Fujimoto, T.; Ban, H.; Bamba, S.; Tsujikawa, T.; Sasaki, M.; Fujiyama, Y.; Andoh, A.
Summary Eotaxins induce the trafficking of eosinophils to the sites of inflammation via CC chemokine receptor 3 (CCR3). In this study, we investigated eotaxin‐3/CC chemokine ligand 26 (CCL26) expression in the inflamed mucosa of patients with inflammatory bowel disease (IBD), and characterized the molecular mechanisms responsible for eotaxin‐3 expression in human colonic myofibroblasts. Eotaxin‐3 mRNA and protein expression was evaluated by real time‐polymerase chain reaction (PCR) and enzyme‐linked immunosorbent assay (ELISA), respectively. Eotaxin‐3 mRNA expression was elevated significantly in the active lesions of ulcerative colitis (UC) patients. Significant elevations were also observed in the active lesions of Crohn's disease (CD) patients, but this was significantly lower than that detected in the active UC lesions. There were no significant increases in the inactive lesions of UC or CD patients. Colonic myofibroblasts were identified as a major source of eotaxin‐3 in the colonic mucosa, and interleukin (IL)‐4 and IL‐13 enhanced eotaxin‐3 mRNA and protein expression significantly in these cells. There was a significant positive correlation between mucosal eotaxin‐3 and IL‐4 mRNA expression in the active lesions of IBD patients. The IL‐4‐ and IL‐13‐induced eotaxin‐3 mRNA expression was regulated by the signal transducer and activator of transcription‐6 (STAT‐6) and suppressor of cytokine signalling (SOCS)1‐mediated pathways. Interferon (IFN)‐γ acts as a negative regulator on the IL‐4‐ and IL‐13‐induced eotaxin‐3 expression via STAT‐1 activation. Eotaxin‐3 expression was elevated specifically in the active lesions of IBD, in particular UC. Eotaxin‐3 derived from colonic myofibroblasts may play an important role in the pathophysiology of UC.